EDUCATION UNIT STRATEGY TO IMPLEMENT HEALTHY SCHOOL PROGRAMS (Jurusan PGPAUD FIP UNNES, 2022)
Kartini Early Childhood Education (PAUD Kartini) implements a healthy school program by developing six aspects of the development field, including learning development, infrastructure development, employment development, partnership development, school management development, and funding development. This research aims to find out the strategies used by PAUD Kartini in implementing healthy school programs. Research methods used is qualitative research method. The results of the study show that there are several factors supporting the implementation of healthy school program including the involvement of other parties, adequate infrastructure, the existence of health services and the existence of health education. Inhibiting factors include student health habit is still lacking, the teachers still need to learn about health, and large funding problem. The conclusion of the study is that PAUD Kartini has a strategy to implement a healthy school program and the presence of supporting factors and inhibitory factors that arise. Keywords: Education Unit, Healthy School, Early Childhood Education (PAUD)